2019
DOI: 10.1136/bmjopen-2018-024265
|View full text |Cite
|
Sign up to set email alerts
|

Public, health professional and legislator perspectives on the concept of psychiatric disease: a population-based survey

Abstract: ObjectiveTo assess which mental health-related states of being are perceived as diseases by psychiatrists, non-psychiatric physicians, nurses, parliament members and laypeople.Design and settingA population-based, mailed survey in Finland.ParticipantsRespondents from a random sample of 3000 laypeople, 1500 physicians, 1500 nurses and all 200 members of the parliament (MPs) of Finland.Primary outcome measuresRespondents’ perspectives on 20 mental health-related states of being as diseases, measuring the extent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 42 publications
(50 reference statements)
0
18
0
1
Order By: Relevance
“…We observed differences in stigma aspects between studies that used labels or vignettes to describe persons with AUD as stimuli. In vignette studies in which a person fulfilling the criteria of a mental disease was described, AUD seemed to be more likely to be considered a mental illness by viewers (60% to 74% in studies #10, #11, #15; Chong et al, 2016; DePierre et al, 2014; Perry et al, 2020), while in the study of Tikkinen, which used the label “alcoholism”, only half of the sample recognized AUD as a disease (Tikkinen et al, 2012, 2019). This underlines the potential impact of applying either a labeling or a vignette‐based approach to capture public stigma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We observed differences in stigma aspects between studies that used labels or vignettes to describe persons with AUD as stimuli. In vignette studies in which a person fulfilling the criteria of a mental disease was described, AUD seemed to be more likely to be considered a mental illness by viewers (60% to 74% in studies #10, #11, #15; Chong et al, 2016; DePierre et al, 2014; Perry et al, 2020), while in the study of Tikkinen, which used the label “alcoholism”, only half of the sample recognized AUD as a disease (Tikkinen et al, 2012, 2019). This underlines the potential impact of applying either a labeling or a vignette‐based approach to capture public stigma.…”
Section: Discussionmentioning
confidence: 99%
“…Six studies investigated whether AUD was considered a disease or a mental illness, with only 5 studies presenting their findings (no information was available for study #12). In the Finnish study by Tikkinen et al, (2012Tikkinen et al, ( , 2019, more than 1500 adults were asked whether they considered a wide range of mental disorders or other conditions to be a disease (label stimulus "alcoholism"). While more than three-quarters indicated that schizophrenia and autism were a disease and more than half of the respondents considered depression, eating disorders, panic disorder, and attention deficit hyperactivity disorder (ADHD) to be diseases, the results were less clear for AUD, drug addiction, social anxiety disorder, generalized anxiety disorder, and insomnia.…”
Section: Labelingmentioning
confidence: 99%
“…More generally, mental health professionals may lack awareness that public understandings of mental disorder may be substantially narrower than their own. Tikkinen et al (2019), for example, recently showed that psychiatrists define a broader set of mental health conditions to be diseases than non-psychiatrist physicians, who in turn had more inclusive concepts than laypeople. Greater awareness of such discrepancies and their clinical implications among professionals might improve treatment engagement and effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…The remaining 10 studies were selected for inclusion in the review. These consisted of four studies from the United States (Lebowitz et al, 2016; Meza et al, 2019; Thompson & Lefler, 2016; Wadian et al, 2019), two studies from Germany (Speerforck, Hertel, et al, 2019; Speerforck, Stolzenburg, et al, 2019), and one study each from Australia (Partridge et al, 2014), Finland (Tikkinen et al, 2019), Korea (Park et al, 2018), and Indonesia (Julivia Murtani et al, 2020). These 10 studies were each assessed for the sample population, sample size, design, and purpose of the study.…”
Section: Resultsmentioning
confidence: 99%